ROBUST AND SECURE DISCRETE WAVELET TRANSFORM BASED WATERMARKING SCHEME TWO-LEVEL SINGULAR VALUE DECOMPOSITION - Tanya Koohpayeh Araghi, 1981-, author; Azizah Abd. Manaf, Prof.Dr., supervisor; Sekolah Informatiks Termaju (Kuala Lumpur : Universiti Teknologi Malaysia, 2016)
Thesis (Ph.D) - Universiti Teknologi Malaysia, 2016